¿Qué educación? ¿Para qué desarrollo? - Morales Basadre, Ricardo (2011)
Education is closely related to progress. lt is necessary to clarify in what sense education contributes to development and in that way to which development we are referring because nowadays in our country, even though it may be dictatorial, it denominates by itself a democratic republic.